2014
DOI: 10.2337/db13-1954
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Defective Insulin Signaling, and Mitochondrial Dysfunction as Common Molecular Denominators Connecting Type 2 Diabetes to Alzheimer Disease

Abstract: A growing body of evidence supports an intriguing clinical/epidemiological connection between Alzheimer disease (AD) and type 2 diabetes (T2D). T2D patients have significantly increased risk of developing AD and vice versa. Recent studies have begun to reveal common pathogenic mechanisms shared by AD and metabolic disorders, notably obesity and T2D. In T2D and obesity, low-grade chronic inflammation is a key mechanism leading to peripheral insulin resistance, which progressively causes tissue deterioration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
333
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(369 citation statements)
references
References 132 publications
8
333
0
4
Order By: Relevance
“…It has been reported that GLP-1 and longer-lasting protease-resistant analogs cross the blood-brain barrier and exert a neuroprotective action in the brains of mouse models of several neurodegenerative diseases, such as Alzheimer disease (28,29). In this regard, several clinical trials (30,31) aimed at exploring the effects of GLP-1R agonists on preventing the development of Alzheimer disease are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GLP-1 and longer-lasting protease-resistant analogs cross the blood-brain barrier and exert a neuroprotective action in the brains of mouse models of several neurodegenerative diseases, such as Alzheimer disease (28,29). In this regard, several clinical trials (30,31) aimed at exploring the effects of GLP-1R agonists on preventing the development of Alzheimer disease are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this increases the appetite and caloric intake by up-regulating the body weight homeostasis in the paraventricular nucleus of the hypothalamus, affecting also cardiovascular functions and blood pressure (de Kloet et al, 2014;Rui, 2013). Altogether, these settings promote neuron injury, resulting in the alteration of cognitive functions (Elias et al, 2003) and may favor neurodegenerative diseases like AD and PD (Bousquet et al, 2012;De Felice and Ferreira, 2014). How brain inflammation is initiated during both obesity and hypertension is a debatable issue, under continuous investigation.…”
Section: Peripheral Diseases: Obesity and Hypertensionmentioning
confidence: 99%
“…Neuroinflammation along with the process of seeding and spread is initiated eventually with neuronal dysfunction, and toxicity ensue [89]. With the event of insulin resistance, defective insulin signaling, and also the mitochondrial dysfunction in the brain, which are the common quirk of T2DM and AD; hamming the questions which one leads the other in the aged people [90][91][92].…”
Section: T2dm and Ad Linkagementioning
confidence: 99%